Digital citizenship: Peran media sosial dalam membentuk opini publik dan partisipasi politik di Indonesia - Azizatuddini, Tazkiya (Maliki Interdisciplinary Journal, 2026)
The era of digitalization has fundamentally transformed how citizens engage in political life. Social media has transcended its role as a mere communication platform to become a new public sphere where political opinions are formed, disseminated, and contested. This article aims to analyze the role of social media in shaping public opinion and fostering citizen political participation in Indonesia, while examining the relevance of digital citizenship as a normative framework needed to optimize the democratic potential of digital media. Using a library research method, this study reviews relevant theoretical and empirical sources. The findings reveal that social media plays a dual role: on one hand, it serves as an instrument of democratization that broadens access to information and public participation; on the other, it is susceptible to exploitation for spreading disinformation, exacerbating political polarization, and undermining social cohesion. In the Indonesian context, this phenomenon has been evident in various electoral contests. The revitalization of digital citizenship grounded in Pancasila values is seen as a crucial strategy for cultivating citizens who are critical, principled, and responsible in their use of digital spaces. Policy implications include strengthening digital literacy education and integrating national values into the social media ecosystem.